Does Inclination of the Toe Proximal Phalangeal Head Affect the Outcomes of Vascularized Joint Transfers? Retrospective Study of 22 Joint Transfers. Issue 4 (29th July 2022) - Pae, Woo Sik; Lin, Yu-Te; Loh, Charles Yuen Yung; Lee, Che-Hsiung; Hsu, Chung-Chen; Chen, Shih-Heng; Lin, Cheng-Hung
Abstract : Background: Different shapes of the proximal phalangeal head of toe proximal interphalangeal joints (e.g., oval and circular) are observed in vascularized joint transfers. The difference in shape implies the varying degrees of inclination of the articular surfaces between toes. This study investigated the impact of articular inclination on outcomes after toe joint transfers for finger proximal interphalangeal joint reconstruction. Methods: Twenty-one patients who underwent vascularized joint transfer from May of 2009 to May of 2018 were included. Their mean age was 33.4 years and mean follow-up period was 28.9 months. All patients had a type I central slip according to the Te classification. Articular surface inclination was measured on lateral radiographic views. Results: Passive range of motion of the toe proximal interphalangeal joint before vascularized joint transfer was 71.1 ± 9.6 degrees. The functional range of motion of the reconstructed proximal interphalangeal joint was 60.0 ± 17.0 degrees. The extensor lag after the joint transfer was 9.4 ± 19.6 degrees. The articular inclination of the toe joint was 71.9 ± 9.7 degrees. A Pearson correlation analysis of all variables, including age, preoperative range of motion of the toe joint, postoperative range of motion of the reconstructed joint, articular inclination of the toe joint, and extensor lag of the reconstructed joint with toe articular inclination, was performed. There was no significant correlation between articular inclination of the toe joint and extensor lag of the reconstructed joint ( p = 0.226). Conclusion: The articular surface inclination of the toe did not affect the functional range of motion after joint transfer. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.